Effect of precipitants on Ni-CeO2 catalysts prepared by a co-precipitation method for the reverse water-gas shift reaction - WANG, Luhui; LIU, Hui; LIU, Yuan; CHEN, Ying; YANG, Shuqing (Journal of rare earths, 2013)
A series of Ni-CeO2 catalysts were prepared by co-precipitation method with Na2CO3, NaOH, and mixed precipitant （Na2CO3：NaOH; 1：1 ratio） as precipitant, respectively. The effect of the precipitants on the catalytic performance, physical and chemical properties of Ni-CeO2 catalysts was investigated with the aid of X-ray diffraction （XRD）, Bmmaner-Emmett-Teller method （BET）, Fou- rier-transform infrared spectroscopy （FT-IR）, thermogravimetry （TG）, and H2-TPR characterizations. The Ni-CeO2 catalysts were exam- ined with respect to their catalytic performance for the reverse water-gas shift reaction, and their catalytic activities were ranked as： Ni-CeO2-CP （Na2CO3：NaOH=I：I）〉Ni-CeO2-CP（Na2CO3）〉Ni-CeO2-CP（NaOH）- Correlating to the characteristic results, it was found that the catalyst prepared by co-precipitation with mixed precipitant （Na2CO3：NaOH; 1：1 ratio） as precipitant hadthe most amount of oxygen vacancies accompanied with highly dispersed Ni particles, which made the corresponding Ni-CeO2-CP（Na2CO3：NaOH=I： 1） catalyst exhibit the highest catalytic activity. While the precipitant of Na2CO3 or NaOH resulted in less or no oxygen vacancies in Ni-CeO2 catalysts. As a result, Ni-CeO2-CP（Na2CO3） and Ni-CeO2-CP（NaOH） catalysts presented poor catalytic performance.